Mahovi kot kazalci vnosa dušikovih spojin v naravne ekosisteme Slovenije in primerjava z nekaterimi drugimi metodami bioindikacije - Skudnik, Mitja (visokošolska dela, 2016)
Samples of moss Hypnum cupressiforme Hedw. were collected at 103 locations in the % forests of Slovenia and analysed for nitrogen (N) and isotopic composition of nitrogen (.15N % value). At each location, mosses were collected at two sites: under the tree canopy and in a % nearby forest clearing. Mosses collected within forest clearing reflect the atmospheric deposition % of N; but we have not found a significant relationship between throughfall deposition of N and % N concentration in mosses that were collected under canopies. .15N value in moss depended % significantly on the ratio of ammonium and nitrate in precipitation in the open, but only under % condition that we excluded the locations which had less than 1000 mm of average annual % precipitation. The results show that N concentrations under the canopy are larger than in the % forest clearings. N concentrations in mosses collected at least three meters away from the nearest % tree canopy projections were on average 41% lower than under the canopy. The results show % that moss collected in forest clearings reflects the characteristics of the surrounding land use and, % consequently, the main sources of N emissions; while for moss collected under the canopy forest, % characteristics at the collecting location are more important than the main emission sources of % N. Regression models were established for predicting N concentration in mosses in forest % clearings depending on N concentration in mosses collected under a canopy and other % environmental variables. The spatial correlation existed only for N in mosses, which have been % collected in forest clearings. In this case, the ordinary kriging was used for spatial interpolation % of the data. Spatial correlation was not found for N in mosses that were collected under the % canopy, nor .15N value in mosses collected at both sampling sites (under the canopy / in the % open). In this case, the spatial interpolation of data was done as the sum of the regression % prediction and inverse distance weighted interpolation of regression residuals. Both maps (N % concentration in moss collected under the forest canopy and in the clearings) show similar areas % with elevated N concentrations. The only exception was that with mosses collected under a % canopy of trees, where also some local emitters of NOx were exposed. Limited statistically % significant correlation existed between the N concentration in mosses and foliar N and crustose % lichens cover. With more negative .15N values in mosses the tree defoliation was lower. Samples of moss Hypnum cupressiforme Hedw. were collected at 103 locations in the forests of Slovenia and analysed for nitrogen (N) and isotopic composition of nitrogen (.15N value). At each location, mosses were collected at two sites: under the tree canopy and in a nearby forest clearing. Mosses collected within forest clearing reflect the atmospheric deposition of N; but we have not found a significant relationship between throughfall deposition of N and N concentration in mosses that were collected under canopies. .15N value in moss depended significantly on the ratio of ammonium and nitrate in precipitation in the open, but only under condition that we excluded the locations which had less than 1000 mm of average annual precipitation. The results show that N concentrations under the canopy are larger than in the forest clearings. N concentrations in mosses collected at least three meters away from the nearest tree canopy projections were on average 41% lower than under the canopy. The results show that moss collected in forest clearings reflects the characteristics of the surrounding land use and, consequently, the main sources of N emissions; while for moss collected under the canopy forest, characteristics at the collecting location are more important than the main emission sources of N. Regression models were established for predicting N concentration in mosses in forest clearings depending on N concentration in mosses collected under a canopy and other environmental variables. The spatial correlation existed only for N in mosses, which have been collected in forest clearings. In this case, the ordinary kriging was used for spatial interpolation of the data. Spatial correlation was not found for N in mosses that were collected under the canopy, nor .15N value in mosses collected at both sampling sites (under the canopy / in the open). In this case, the spatial interpolation of data was done as the sum of the regression prediction and inverse distance weighted interpolation of regression residuals. Both maps (N concentration in moss collected under the forest canopy and in the clearings) show similar areas with elevated N concentrations. The only exception was that with mosses collected under a canopy of trees, where also some local emitters of NOx were exposed. Limited statistically significant correlation existed between the N concentration in mosses and foliar N and crustose lichens cover. With more negative .15N values in mosses the tree defoliation was lower.
Keywords: Onesnaževanje okolja; Dušik; Disertacije; natural environment; Okolje; Onesnaženost; pollution; Bioindikacija; biomonitoring; bioindikatorji; dušikove spojine; gozdovi; Slovenia; Slovenija; izotopska sestava; krošnja; gozdne vrzeli; raba tal; onesnaževalci; modeliranje